Исследование задач о рекуррентных последовательностях, входящих в состав психологических тестов - Юрий Владимирович Чебраков (Психология. Журнал Высшей школы экономики, 2011)
Seventeen items of recurrent sequences of psychological test of R. Cattel and «Numeric test» of H. Eysenk were investigated from the position of general theory of recurrent relationships. It was demonstrated that tasks with ambiguous answers were to be found among the mentioned items. For this type of tasks new formulations were given which allows to eliminate uncertainty of response.